Factors influencing career plateau in nurses: a protocol for systematic review and meta-analysis - Jia Chen; Shuang Hu; Xiaochen Yan; Wenjun Chen; Jiajia Liu; Qian Zhang; Xincen Liu; Xiaoyu Du; Ruixue Hui; Wendi Guo (BMJ Open, 2025)
Introduction Career plateau is a situation that has many negative effects on individual nurses, nursing management and nursing profession. Despite global research examining career plateaus among nurses, a comprehensive data synthesis on its prevalence and influential factors is still missing. The study aims to systematically analyse the prevalence of career plateau in nurses and explore the related influencing factors.Methods and analysis The anticipated start date for the study is December 2025, and the anticipated end date is August 2027. We will search PubMed, Web of Science, Embase, PsycINFO, CINAHL, Scopus, the China National Knowledge Infrastructure, the Wanfang database and the China Biomedical Literature Database (SinoMed) from the establishment of the database to the present for studies on the prevalence and influencing factors of career plateau in nurses. Two researchers will independently conduct literature screening and data extraction. They will evaluate the quality of the included studies using the Joanna Briggs Institute critical appraisal tool and the mixed-methods appraisal tool. If possible, we will conduct a meta-analysis, which is according to the data heterogeneity. If the heterogeneity is too large to be resolved, we will present them narratively and descriptively according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses criteria, summarise status and influencing factors of the career plateau in nurses.Ethics and dissemination No formal ethics approval is required for this protocol and no primary data will be collected. The results will be disseminated through peer-reviewed journals and presented at conferences.PROSPERO registration number CRD42024545439.